Determining features of application of functional electrochemical coatings in technologies of surface treatment - Karakurkchi, Ann; Sakhnenko, Mykola; Ved’, Maryna; Yermolenko, Iryna; Pavlenko, Sergey; Yevsieiev, Vadym; Pavlov, Yaroslav; Yemanov, Vladislav (Eastern-European Journal of Enterprise Technologies, 2019)
Approaches to the use of electrochemical coatings in surface treatment technologies are analyzed. It is shown that directed surface modification allows expanding the functional properties of the treated material, in particular, increasing the strength, wear resistance, corrosion resistance, catalytic activity. The method for treating non-alloy steel and cast irons by forming thin-film coatings of ternary alloys of iron and cobalt with molybdenum and tungsten is proposed. It is shown that the incorporation of refractory metals up to 37 at. % into the surface layer leads to a change in the phase structure of the coating. This is found to provide an increase in wear resistance by 40 %, microhardness by 2.5–3.5 times, as well as a decrease in friction coefficient by 3–4 times in comparison with the substrate material. The resulting materials can be used for hardening and protection of surfaces in various industries. To modify the surface of piston silumins, it is proposed to use the method of plasma electrolytic oxidizing with the formation of ceramic-like coatings. It is shown that in the galvanostatic mode, from alkaline electrolyte solutions containing manganese and cobalt salts, it is possible to obtain uniform, dense, highly adhesive to the base metal, oxide coatings, doped with catalytic components whose content varies within 25–35 at. %. It is shown that the morphology and phase structure of the surface layers changes with the incorporation of dopant metals. The formed coatings have a high degree of surface development, which is a prerequisite for enhancing their functional properties. The proposed approach is used to modify the surface of the KamAZ-740 piston. It is found that the use of ceramic-like coatings of the engine piston leads to a decrease in hourly fuel consumption and amount of toxic substances with exhaust gases, which makes them promising for use in in-cylinder catalysis.